블레이드 손상에 따른 이축식 터보팬 엔진의 동적 안정성 해석 - 김시태(Sitae Kim); 정기현(Kihyun Jung); 이준호(Junho Lee); 박기현(Kihyun Park); 양광진(Kwangjin Yang) (Tribology and Lubricants, 2020)
This paper presents a numerical study on the rotordynamic analysis of a dual-spool turbofan engine in the context of blade defect events. The blades of an axial-type aeroengine are typically well aligned during the compressor and turbine stages. However, they are sometimes exposed to damage, partially or entirely, for several operational reasons, such as cracks due to foreign objects, burns from the combustion gas, and corrosion due to oxygen in the air. Herein, we designed a dual-spool rotor using the commercial 3D modeling software CATIA to simulate blade defects in the turbofan engine. We utilized the rotordynamic parameters to create two finite element Euler-Bernoulli beam models connected by means of an inter-rotor bearing. We then applied the unbalanced forces induced by the mass eccentricities of the blades to the following selected scenarios: 1) fully balanced, 2) crack in the low-pressure compressor (LPC) and high pressure compressor (HPC), 3) burn on the high-pressure turbine (HPT) and low pressure compressor, 4) corrosion of the LPC, and 5) corrosion of the HPC. Additionally, we obtained the transient and steady-state responses of the overall rotor nodes using the Runge-Kutta numerical integration method, and employed model reduction techniques such as component mode synthesis to enhance the computational efficiency of the process. The simulation results indicate that the high-vibration status of the rotor commences beyond 10,000 rpm, which is identified as the first critical speed of the lower speed rotor. Moreover, we monitored the unbalanced stages near the inter-rotor bearing, which prominently influences the overall rotordynamic status, and the corrosion of the HPC to prevent further instability. The high-speed range operation (>13,000 rpm) coupled with HPC/HPT blade defects possibly presents a rotor-case contact problem that can lead to catastrophic failure.